Determinant Factors of Fertility in Reproductive Age Women - Rindang Ekawati; Laili Rahayuwati; Ikeu Nurhidayah; Habsyah Saparidah Agustina; Endah Rahayu (Jurnal Keperawatan Padjadjaran, 2019)
The target of the 2015 Medium-Term National Development Plan is the fertility rate of 2.1 children. However, based on The Indonesian National Demographic and Health Survey 2017, the fertility rate of West Java Province is similar to the national, which is 2.4 children. West Java is a barometer of the national fertility rate since one-fifth of Indonesia's population is in West Java. This study aims to analyze the factors that influence fertility (number of children ever born). The design of this study was cross-sectional. Data derived from the 2018 Survey of Accountability Programs Performance covered 12,350 women aged 15-49 years. The sample was 9,814 woman who had been married. Data analysis used univariate, bivariate and multivariate analyses with a confidence level of 0.05. Bivariate results found that five variables that affected fertility were the age of first marriage, frequency of marriage, use of contraceptive, ideal family size, and wealth index, while the area of residence was not related to fertility. Indeed there are three most dominant factors that have been related to fertility were the age of first marriage, frequency of marriage, and the use of contraceptives. The conclusion was that women who marry at an older age and use contraception have lower fertility rates.  This study can be considered in population control policies, especially to improve health promotion programs regarding the ideal marriage age for women and the use of contraception as an effort to control the population rate.  This study can be considered in population policies.